ALK-rearranged non-small cell lung cancers: how best to optimize the safety of crizotinib in clinical practice?. Issue 2 (February 2014) - Girard, Nicolas; Audigier-Valette, Clarisse; Cortot, Alexis B; Mennecier, Bertrand; Debieuvre, Didier; Planchard, David; Zalcman, Gérard; Moro-Sibilot, Denis; Cadranel, Jacques; Barlési, Fabrice
<x xml:space="preserve">Abstract</x> Crizotinib (XALKORI™, Pfizer) is a tyrosine kinase inhibitor targeting ALK, MET and ROS1, currently approved for the treatment of adults with ALK-rearranged non-small-cell lung cancer. Optimizing the management of frequent crizotinib-related adverse events is crucial to ensure its continuous administration and reproduce the response and survival rates reported in clinical trials. Here, we propose some practical measures, which are mostly derived from the recommendations given to the investigators of the PROFILE 1001, 1005, 1007 and 1014 trials and are based on experience and scientific findings regarding the management of these disorders. While visual disturbances or bradycardia are frequent but benign, the severity of the cardiac and hepatic adverse events requires special attention potential to QT interval prolongations and to the monitoring of electrolyte levels and liver function, taking into account potential drug–drug interactions.